2020
DOI: 10.1177/2633105520906402
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Expression of Receptor-Interacting Protein Kinase 1 in Secondary Neural Tissue Damage Following Spinal Cord Injury

Abstract: Introduction: Necroptosis is a form of programmed cell death that is different from apoptotic cell death. Receptor-interacting protein kinase 1 (RIPK1) plays a particularly important function in necroptosis execution. This study investigated changes in expression of RIPK1 in secondary neural tissue damage following spinal cord injury in mice. The time course of the RIPK1 expression was also compared with that of apoptotic cell death in the lesion site. Methods and Materials: Immunostaining for RIPK1 was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Our results are in line with previous findings suggesting that upregulated RIPK1 expression may provide an essential mechanism for the pathogenesis of neuropathic pain. Increased RIPK1 expression has been observed in various types of neuropathic pain in rats harboring a spinal cord injury [ 6 , 7 ] or sciatic nerve injury [ 8 , 9 ]. Moreover, the intraperitoneal administration of Nec-1 was reported to ameliorate both mechanical allodynia and hyperalgesia in a rat model of sciatic nerve injury [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in line with previous findings suggesting that upregulated RIPK1 expression may provide an essential mechanism for the pathogenesis of neuropathic pain. Increased RIPK1 expression has been observed in various types of neuropathic pain in rats harboring a spinal cord injury [ 6 , 7 ] or sciatic nerve injury [ 8 , 9 ]. Moreover, the intraperitoneal administration of Nec-1 was reported to ameliorate both mechanical allodynia and hyperalgesia in a rat model of sciatic nerve injury [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence supports the involvement of RIPK1 in the processes underlying nociceptive information. RIPK1 expression significantly increases at the site of injury following a spinal cord laminectomy [ 6 ], a spinal cord injury [ 7 ], and in a chronic constriction injury model [ 8 , 9 ]. Moreover, a blockade of RIPK1 expression alleviates hyperalgesia and mechanical allodynia in rats with sciatic nerve injury [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our results also showed that the number of LAMP2A-expressing cells increased from 24 h and peaked at 3 days, lasting for at least 7 days after injury. The time course of LAMP2A expression is similar to that of apoptosis after SCI [ 112 , 113 , 114 ]. Apoptosis is considered a major cause of secondary damage following SCI [ 112 , 114 ].…”
Section: Acute Neurological Insults and Cmamentioning
confidence: 99%
“…Following acute neurological insults to the CNS, including cerebral infarction, TBI and SCI, secondary injury can be induced by various molecular mechanisms, such as oxidative stress and neuroinflammation in the brain and spinal cord [ 132 , 133 ]. Such secondary injury is involved in multiple pathologies associated with neural cell death and neurodegeneration, aggravating the initial tissue damage of the CNS [ 112 , 113 , 132 ]. The secondary damage can be a potential therapeutic target for effective treatment of acute neurological insults to the CNS.…”
Section: Therapeutic Potential Of Cma For Acute Neurological Insultsmentioning
confidence: 99%
“…Although TBI and SCI are capable of sharing numerous identical pathophysiology-related characteristics, the temporal patterns of RIPK1/RIPK3 and MLKL expression between SCI and TBI differ. Kanno et al investigated the time course of RIPK1 protein expression state inside impaired neural tissue after SCI and reported that the increase in RIPK1 expression was initiated at 24 h, peaked at 3 days, and continued for 7 days after SCI [58] . Interestingly, Liu et al found that unlike RIPK1, the levels of RIPK3 and MLKL protein rose markedly at 1 day but decreased by day 3 after injury [59] .…”
Section: Involvement Of Necroptosis In Cns Traumamentioning
confidence: 99%